2021
DOI: 10.1088/1751-8121/ac0546
|View full text |Cite
|
Sign up to set email alerts
|

PT symmetric evolution, coherence and violation of Leggett–Garg inequalities

Abstract: We report an unusual buildup of the quantum coherence in a qubit subjected to non-Hermitian evolution generated by a parity-time () symmetric Hamiltonian, which is reinterpreted as a Hermitian system in a higher dimensional space using Naimark dilation. The coherence is found to be maximum about the exceptional points (EPs), i.e. the points of coalescence of the eigenvalues as well as the eigenvectors. The nontrivial physics about EPs has been observed in various systems, particularly in photonic systems. As a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…PT-symmetric Hamiltonians have attracted wide attention due to their interesting features, and numerous studies have been performed including increase or restoration of entanglement by a local PT-symmetric Hamiltonian [12,14], protecting quantum correlations via non-hermitian operations [15], no-signaling principle violation [16,17], observing fast evolution in a PTsymmetric system [18,19] and observing critical phenomena in a PT-symmetric system [20,21]. Recently, it has been shown that quantum coherence is increased in a single-qubit system under PT-symmetric Hamiltonian and maximal quantum coherence is observed at the exceptional point [22,23]. The flow of quantum coherence of a single qubit under PT-symmetric and anti-PTsymmetric Hamiltonians has been demonstrated on an optics system [24].…”
Section: Introductionmentioning
confidence: 99%
“…PT-symmetric Hamiltonians have attracted wide attention due to their interesting features, and numerous studies have been performed including increase or restoration of entanglement by a local PT-symmetric Hamiltonian [12,14], protecting quantum correlations via non-hermitian operations [15], no-signaling principle violation [16,17], observing fast evolution in a PTsymmetric system [18,19] and observing critical phenomena in a PT-symmetric system [20,21]. Recently, it has been shown that quantum coherence is increased in a single-qubit system under PT-symmetric Hamiltonian and maximal quantum coherence is observed at the exceptional point [22,23]. The flow of quantum coherence of a single qubit under PT-symmetric and anti-PTsymmetric Hamiltonians has been demonstrated on an optics system [24].…”
Section: Introductionmentioning
confidence: 99%
“…1 (Left)). Recently it has been shown that K 3 can take values upto its algebraic bound in case of a TLS undergoing non-Hermitian dynamics (PT-symmetric with fixed eigenspectrum) 20,21 and close to the exceptional point in the PT-symmetric phase 22 . Whereas we explore the non-Hermitian dynamics of a TLS across the exceptional point separating the PT-symmetric and PTbroken phases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using PT$\mathcal {PT}$‐symmetric evolution, [ 43 ] it has been shown that the quantum violation of standard LGIs in quantum theory can approach the algebraic maximum for four‐time [ 61 ] as well as three‐time LGI [ 62 ] scenarios. In ref.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [62], one of us has shown the enhancement of coherence around the exception point of PT$\mathcal {PT}$‐symmetric systems and its impact on the degree of violation of LGIs. Although our work is along this line, we additionally study the quantum violation of the variant of LGIs in a three‐time LG scenario.…”
Section: Introductionmentioning
confidence: 99%